Environmental and Behavioral Factors with Refractive Error in Israeli Boys. Issue 8 (August 2021) - Gordon-Shaag, Ariela; Shneor, Einat; Doron, Ravid; Levine, Jonathan; Ostrin, Lisa A.
Abstract : SIGNIFICANCE: Evidence supporting the contributions of near work in myopia is equivocal. Findings from this pilot study suggest that a high prevalence of myopia in ultra-Orthodox boys may be attributed to intense near work at school and learning to read in preschool at an early age. PURPOSE: This study aimed to assess factors that may influence myopia in three groups of Jewish boys with different educational demands. METHODS: Healthy ultra-Orthodox, religious, and secular Jewish boys (n = 36) aged 8 to 12 years participated. Refractive status, education, time spent reading and writing, and electronic device use were assessed using a questionnaire, and time outdoors and physical activity were assessed objectively using an Actiwatch. Data were analyzed with χ 2 and Kruskal-Wallis tests with Bonferroni post hoc comparisons. RESULTS: Ultra-Orthodox (n = 14) and religious (n = 13) children had greater myopia prevalence compared with secular children (n = 9; P = .01), despite no differences in parental myopia. Actigraph data showed that there were no differences in activity ( P = .52) or time spent outdoors ( P = .48) between groups. Ultra-Orthodox children learned to read at a younger age and spent more hours at school ( P < .001 for both). All groups engaged in a similar amount of near work while not in school ( P = .52). However, ultra-Orthodox boys had less electronic device use than did religious ( P = .007) and secular children ( P < .001). CONCLUSIONS: This pilot study demonstrates that ultra-Orthodox, religious, and secular children have distinct educational demands but similar time outdoors, physical activity, and near work while not in school. The findings suggest that near work at school and/or learning to read in preschool at an early age may contribute to previously reported differences in refractive error between groups. However, conclusions should be confirmed in a larger sample size. Abstract : Supplemental digital content is available in the text.